(untitled) (KYAMC Journal, 2013)
Patients with type 2 diabetes mellitus (T2DM) are usually treated with pharmacologic agents in combination with lifestyle modification. Recently new antidiabetic drugs have been introduced to supplement the older therapies, such as insulin, sulfonylureas, and metformin, thereby increasing the number of treatment options by the practitioners and patients which has heightened uncertainty regarding the most appropriate means of treating this widespread disease. The development of antidiabetic agents in this millennium, like insulin analogs, incretin-based therapies Dipeptidyl Peptidase-4 (DPP-4) inhibitors & Glucagon like peptide-1 (GLP-1) analogs, colesevelam, bromocriptine and pramlintide has also led to treatment strategies that enable many patients with T2DM to achieve target HbA1c levels (<7.0%). Pharmacologic treatment of patients with T2DM is limited not only by the effectiveness or adverse effects of the agent but also by the cost, patient’s preferences, needs, and values. This review article discusses the current pharmacological agents, their latest successes, demerits and limitations in the treatment of patients with T2DM. This article also reviews the different updated guidelines, treatment algorithms, and recommendations provided for the management of T2DM by expert committees of different associations and federations. In June 2012, American Diabetes Association (ADA) & European Association for the Study of Diabetes (EASD) has described patient centered approach in the management of T2DM and stressed importance to individualize treatment targets. More stringent HbA1c targets (e.g., 6.0-6.5%) might be considered in selected patients. Conversely, less stringent HbA1c goals-e.g., 7.5-8.0% or even slightly higher-are appropriate for some other patients. International Diabetes Federation (IDF) document in 2011, however, concentrates on the role of postprandial hyperglycemia and calls also for HbA1c target value of 7.0%. It is generally agreed that metformin, if not contraindicated and if tolerated, is the preferred and most cost-effective first line agent for the treatment of T2DM. Metformin is cheaper than most other pharmacologic agents, has better effectiveness, and is associated with fewer adverse effects; of note, it does not result in weight gain. DOI: http://dx.doi.org/10.3329/kyamcj.v3i1.13661 KYAMC Journal Vol. 3, No.-1, June 2012 pp.250-261